The effects of recruitment and promotion practices on employees’ job satisfaction in the local governments / Adnan Aminuddin and Mahazril ‘Aini Yaacob - Aminuddin, Adnan; Yaacob, Mahazril ‘Aini (Universiti Teknologi MARA, Kedah, 2011)
Human resource practices are usually associated with the continuous organization’s operation and succession. In order to succeed, an organization must prioritize the welfare of their employees as they are the key players in determining the prosperity of the organization. Hence, employees’ job satisfaction is the focal point in retaining the employees and organization’s succession. This study tries to identify the effects of human resource practices towards employees’ job satisfaction. The respondents in this research were employees from five selected local governments in Northern Region in Malaysia. There are two independent variables used which are Recruitment and Promotion. The findings of this study show that there are positive significant relationship between recruitment and promotion towards employees’ job satisfaction but only at a moderate level. Due to this reason, local governments must increase the effort to maximize the satisfaction level among employees by stressing on their recruitment and promotional practices.